2008
DOI: 10.1093/jac/dkn393
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the combination of α-helical antimicrobial peptides and rifampicin in three rat models of Pseudomonas aeruginosa infection

Abstract: Our results highlight the potential usefulness of these combinations that provide future therapeutic alternatives in P. aeruginosa infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…as well (19). Our observations are consistent with the work of Cirioni et al, who similarly reported a synergistic effect between rifampin and ␣-helical AMPs (magainin II and cecropin A) in Pseudomonas aeruginosa infection models in rats (25). It was hypothesized that AMPs allow rifampin, an RNA polymerase inhibitor, to access its intracellular target by permeabilization of the bacterial membrane (19,36).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…as well (19). Our observations are consistent with the work of Cirioni et al, who similarly reported a synergistic effect between rifampin and ␣-helical AMPs (magainin II and cecropin A) in Pseudomonas aeruginosa infection models in rats (25). It was hypothesized that AMPs allow rifampin, an RNA polymerase inhibitor, to access its intracellular target by permeabilization of the bacterial membrane (19,36).…”
Section: Discussionsupporting
confidence: 91%
“…Infected mice were treated once a day with eCATH1 (1 mg/kg body weight; group I), rifampin (10 mg/kg body weight; group II), a combination of both in the same concentrations as mentioned above (group III), or the same volume of isotonic sodium chloride (control group) for 7 days. The doses, periodicities, and route of injections were chosen based on previous reports (24)(25)(26). Five mice per group were sacrificed 1, 4, and 8 days postinfection (i.e., at the start, middle, and end of treatment), and their spleens and livers were aseptically removed.…”
Section: Methodsmentioning
confidence: 99%
“…AMPs that target membranes are less likely to be rendered ineffective by resistance, because redesigning the microbial membrane architecture cannot be achieved by simple mutations (13,17). Furthermore, combinations of AMPs with traditional antibiotics may achieve enhanced or synergistic activity against bacterial pathogens (18)(19)(20).…”
mentioning
confidence: 99%
“…Magainin II shows a synergistic effect with cecropin peptides (cecropin A and B) 9 , inhibit cell proliferation and viability in a dose dependent fashion in bladder cancer cells 10 . However, there is no report on the use of magainin peptides for treatment against colorectal cancer (CRC).…”
Section: Introductionmentioning
confidence: 99%